Solve x-3t=6 and 4x+3t=9

1 answer

well, we know that x = 3t+6, so use it:

4(3t+6)+3t = 9
12t+24+3t = 9
15t = -15
t = -1
so, x = 3t+6 = 3
Similar Questions
  1. Combine like terms:-3x^2+2x-4x^2-9+6x-2x^2+8 Solve for x: 8x-11= -11x+18 Solve for x: -2(x-5)+7=z-8-5x Solve for x: (x-2)/5 -
    1. answers icon 8 answers
  2. Solve the indicated variable:1. Volume of a cone: solve for h: V=¨ir^2h/3 2. Temperature formula: solve for C: F=9/5C+32
    1. answers icon 1 answer
  3. Put in the correct orderSolve exponentiation. Solve multiplication and division. Solve operations within parentheses Solve
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions